Capturing Emotion And Meaning: The Use Of Imagery In The Lyrics Of D'Masiv'S Perubahan Album - Choeirul Azhar (Asosiasi Dosen Muda Indonesia, 2025)
This study explores the poetic depth of D'Masiv's iconic album Perubahan through a stylistic approach, focusing on the use of diverse imagery. By examining auditory, visual, and emotional imagery, the research reveals how the band constructs a compelling narrative of love, hope, and the realities of adolescent relationships. Often overlooked, pop song lyrics are shown to possess literary richness worthy of serious analysis particularly those with high poetic value, such as D'Masiv’s work. The analysis dissects specific lyric excerpts to demonstrate how the imagery evokes emotion and stimulates the listener’s imagination, creating a cinematic experience that goes beyond mere listening. The novelty of this study lies in its focus on an album deeply rooted in the ears and emotions of “Masivers” and the broader public an object rarely examined from a stylistic perspective. The findings affirm that pop music is not merely a form of entertainment but also an artistic medium rich in literary elements, deserving of scholarly attention. Furthermore, this research offers fresh insights into the linguistic nuances of Indonesian pop lyrics and serves as a valuable reference for musicians, lyricists, educators, and music enthusiasts seeking to deepen their understanding and appreciation of D'Masiv’s poetic expression